The New Concept of Univentricular Heart - Frescura, Carla; Thiene, Gaetano (Frontiers in Pediatrics, 2014)
The concept of univentricular heart moved from hearts with only one ventricle connected with atria (double inlet ventricle or absent AV connection) to hearts not amenable to biventricular repair, namely hearts with two ventricles unable to sustain separately pulmonary and systemic circulations in sequence. In the latter definition, even hearts with one hypoplastic ventricle are considered “functional” univentricular hearts. They include pulmonary or aortic atresia, severe stenosis, and rare conditions like huge intramural cardiac tumors and Ebstein anomaly with extreme atrialization of RV cavity. In this setting, the surgical repair is univentricular with “Fontan” operation, bypassing the ventricular mass. The cases of anatomically true univentricular hearts (double inlet or absent AV connection) almost invariably show two ventricular chambers, one main and one accessory, which lacks an inlet portion. The latter is located posteriorly when morphologically left and anteriorly when morphologically right. As far as double inlet LV, this is usually associated with discordant VA connection (transposition of the great arteries). All the blood flow to the aorta, which takes origin from the hypoplastic anterior RV, is ventricular septal defect (bulbo-ventricular foramen) dependent. If restrictive, an aortic arch obstruction may be present. Double inlet LV may be associated with VA concordance (Holmes heart). As far as double inlet RV with posterior hypoplastic LV cavity, ventriculo- arterial connection is usually of double outlet type. Thus the term double inlet-outlet RV may be coined. In this condition, the contra lateral patent AV valve, may be either mitral or tricuspid in terms of morphology and the underlying ventricle (main chamber) either morphologically left or right. Establishing the loop, whatever right or left (also called right or LV topology), is a fundamental step in the segmental-sequential analysis of congenital heart diseases.